Pottery use in the mining site of variscite Mines de Gavà (Barcelona, Spain) during the 4th millennium BC based on organic residue analysis. (August 2021) - Tarifa-Mateo, N.; Regert, M.; Craig, O.E.; Rosell-Melé, A.; Clop, X.; Saña, M.
Highlights: Terrestrial animal adipose fats were identified in most of the vessels. The oldest evidence of beeswax on pottery surface in the Iberian Peninsula. Alternative uses for the detected animal fat and beeswax are proposed. Abstract: Residue analysis in pottery usually concerns habitat or funerary sites. In this work, we have studied 21 vases from the Mines of Gavà (Barcelona, Spain) which constitute the oldest evidence of mining focused on variscite during the IV th millennium BC. The main objectives are determining the degree of preservation of lipids in this context, identifying the natural substances exploited in the vessels and highlighting pottery use in the day-to-day mining work at this site, as well as establishing if some of the vessels are part of the grave goods from burials in the same mines. The results obtained by combining molecular and isotopic analyses showed that>70% of the containers investigated provided significant amounts of lipids. A wide diversity of organic substances processed comprising animal adipose fats, plants and beeswax was determined. Relationships found between the shape of the vessels and their content highlighted their role in the mining life. This work not only exposes one of the oldest evidences of the use of beeswax in pottery in the Iberian Peninsula, but also allows us to understand the management of resources in a very specialized archaeological site focused on mining activities.